Digital marketing: how the beauty market has changed with the emergence of digital influencers - Genú, Lorena Silveira Batista (2019)
Digital influencers are now one of the primary sources of data to which customers turn when seeking advice and suggestions for pre-purchase in a globe characterized by intense competition. The growing power of digital influencers in the industries where they work can increasingly be realized. The brands should attract customers to their primary goal: sales growth. It is possible in many forms, but digital influencers are one of the most precious strategies. It is because digital influencers have a closer connection with clients. Thus, for instance, bloggers and YouTubers are anticipated to have the confidence of their followers, which is very difficult to hope from any other brand promoter. The ultimate objective of strategy type is to induce those followers to purchase their products and remain loyal to the brands. In this context, this research seeks to define possible implications of the followers-blogger relationship on the buying conduct of followers of beauty bloggers. The goal is to formulate feasible theories from information observation using inductive reasoning and a methodology combining quantitative and qualitative methods. Although hard to assess, they proved to be a pushed source of data that every customer of cosmetics has in the account. Concerning purchase decisions, the more evident trend is the introduction of brands and new products. The latter has shown the marketing ability of bloggers to generate requirements. All the follower-blogger interaction improves the interest of followers in beauty products and thus boosts the number of products bought per year.